A Conjugated Polymeric Supramolecular Network with Aggregation‐Induced Emission Enhancement: An Efficient Light‐Harvesting System with an Ultrahigh Antenna Effect. (3rd September 2019) - Xu, Linxian; Wang, Zaiyu; Wang, Rongrong; Wang, Lingyun; He, Xuewen; Jiang, Huanfeng; Tang, Hao; Cao, Derong; Tang, Ben Zhong
Abstract: Superior artificial light‐harvesting systems (ALHSs) require exceptional capacity in harvesting light and transferring energy. In this work, we report a novel strategy to build ALHSs with an unprecedented antenna effect (35.9 in solution and 90.4 in solid film). The ALHSs made use of a conjugated polymeric supramolecular network (CPSN), a crosslinked network obtained from the self‐assembly of a pillar[5]arene‐based conjugated polymeric host (CPH ) and conjugated ditopic guests (Gs). The excellent performance of the CPSN could be attributed to the following factors: 1) The "molecular wire effect" of the conjugated polymeric structure, 2) aggregation‐induced enhanced emission (AEE) moieties in the CPH backbone, and 3) high capacity of donor–acceptor energy transfer, and 4) crosslinked structures triggered by the host–guest binding between Gs and CPH . Moreover, the emission of the CPSN could be tuned by using different Gs or varying the host/guest ratio, thus reaching a 96 % sRGB area. Abstract : Du bist die Antenne : Ein konjugiertes polymeres supramolekulares Netzwerk mit aggregationsinduzierter Emissionsverstärkung wurde als exzellentes System zum Einfangen von Licht mit beispiellosem Antenneneffekt entwickelt (35.9 in Lösung und 90.4 in festem Film). Des Weiteren konnte die Emission dieses Netzwerkes so abgestimmt werden, dass ein sRGB‐Bereich von 96 % erreicht wurde.